Single-cell Sequencing in the Field of Stem Cells - Chen, Tian; Li, Jiawei; Jia, Yichen; Wang, Jiyan; Sang, Ruirui; Zhang, Yi; Rong, Ruiming (Current Genomics, 2020)
Variation and heterogeneity between cells are the basic characteristics of stem cells. Traditional sequencing analysis methods often cover up this difference. Single-cell sequencing technology refers to the technology of high-throughput sequencing analysis of genomes at the single-cell level. It can effectively analyze cell heterogeneity and identify a small number of cell populations. With the continuous progress of cell sorting, nucleic acid extraction and other technologies, single-cell sequencing technology has also made great progress. Encouraging new discoveries have been made in stem cell research, including pluripotent stem cells, tissue-specific stem cells and cancer stem cells. In this review, we discuss the latest progress and future prospects of single-cell sequencing technology in the field of stem cells.
Keywords: heterogeneity